Tei index of myocardial performance in conscious healthy Beagles - Sousa, M. G.; Pereira-Neto, G. B.; Bruler, B. C.; Paulin-Junior, D.; Pascon, J. P. E.; Gava, F. N. [UNESP]; Carareto, R.; Camacho, A. A. [UNESP] (Univ Austral Chile, Fac Ciencias Veterinarias, 2016)
The Tei index of myocardial performance is a noninvasive echocardiographic parameter that combines systolic and diastolic time intervals to assess global cardiac performance. It was demonstrated to be a reliable indicator of myocardial dysfunction in dogs with varying clinical conditions. Because only a few studies focused on the measurement of the index in healthy dogs, this cross-sectional study was conceived to investigate how it performs in a large population of clinically healthy Beagle dogs. Our results showed no correlation between the index and body weight, heart rate, and several standard echocardiographic measures which are estimates of preload and afterload. There was no difference between de index calculated for males or females. Also, results indicated strong intra-observer and inter-observer correlations. In conclusion, the Tei index was shown to perform independently of loading conditions, besides being a straightforward and easily reproducible parameter.
Keywords: echocardiography; cardiac function; Doppler; dog